Evolucion de los residuos de tres insecticidas en la lucha contra el barrenador de la alcachofa - Beltran, V.=700 1 Coscolla, R.; Gamon, M.; Pelegri, R.; Badia, V.
(Es, En)
ilus., 10 ref.
Keywords: GORTHYNA XANTENES; INSECTA; INSECTOS DAÑINOS DEL TALLO; ALCACHOFA; CONTROL QUIMICO; INSECTICIDAS; RESIDUOS; DIAZINON; MONOCROTOFOS; ESPAÑA